Assessing Environmental Sustainability Across Coastal Tourism Routes in North Jakarta - Ismayanti Ismayanti; Syifa Rahmah (Journal of Enterprise and Development (JED), 2025)
Purpose: This research aimed to compile a ranking of the conditions of existing tourism destinations and assess the level of environmental sustainability across the twelve coastal tourism destination routes in North Jakarta.Method: The study employed a descriptive research design with a quantitative approach, utilizing scoring techniques based on the Barometer of Tourism Sustainability (BTS) performance scale. Data were collected through observations and in-depth interviews with key informants from the selected twelve coastal tourism destination routes in North Jakarta. The research variables were derived from governmental guidelines pertaining to sustainable tourism destinations, encompassing natural conservation, resource management, and waste and emission management.Result: The findings identified the Ancol area as the highest-ranked destination in terms of environmental sustainability, thereby positioning it as a desirable location. Conversely, Muara Angke and Bahtera Jaya Yacht Club were ranked as the lowest and deemed unsustainable destinations. Overall, the environmental sustainability level of the twelve coastal tourism destinations was categorized as potentially unsustainable due to notable deficiencies in resource management, waste management, and emission management.Practical Implications for Economic Growth and Development: The findings provide significant insights for policymakers. Initiatives promoting renewable energy, encouraging the use of public transportation by visitors, and fostering circular economies through sustainable production practices represent viable actions for stakeholders. Given recent constraints, future research is recommended to explore additional aspects of sustainability and to assess the potential impacts of emerging destinations in North Jakarta.Originality/Value: This study contributes novel insights into the relationship between destination development guidelines and environmentally sustainable practices within the context of the twelve coastal tourism destinations in North Jakarta.